A Case of Rickettsia felis Infection Imported From Nepal. Issue 4 (17th April 2015) - Sulis, Giorgia; Rodari, Paola; Caligaris, Silvio; Tomasoni, Lina R.; Castelli, Francesco; Gulletta, Maurizio
<x xml:space="preserve">Abstract</x> Rickettsia felis is an emerging spotted fever group pathogen that may be responsible for potentially life‐threatening infections. A cosmopolitan distribution has been postulated though most human cases were observed in Africa and the Americas. We report an imported case from Nepal that occurred in an Italian tourist who presented with a 1‐week history of fever, headache, nausea, vomiting, and a mild maculopapular rash 14 days after return.